Exploring students’ critical reading development through digital texts: a mixed methods study in indonesian efl context - Zulhidah Zulhidah (Indonesian Institute For Counseling, Education and Therapy, 2026)
ritical reading has become a decisive academic competence in an information environment dominated by digital texts, yet many learners of English as a Foreign Language (EFL) read online material passively rather than critically. Because a single method can establish either how well students read or why they read as they do, but not both, this study adopted an explanatory sequential mixed methods design, pursuing three linked objectives: a quantitative objective to measure the level of students’ critical reading across five dimensions, a qualitative objective to explain the strategies underlying that level, and an integrative objective to generate meta-inferences connecting the two. In Phase 1, 20 undergraduates in one English Education program at Universitas Islam Negeri Sultan Syarif Kasim Riau completed a 10-item Likert questionnaire whose content validity was confirmed by three expert reviewers (scale-level CVI = .92) and whose internal consistency was good (Cronbach’s α = .86); responses were analyzed using descriptive statistics. In Phase 2, 10 students selected for maximum variation on their scores took part in semi-structured interviews analyzed thematically following Braun and Clarke, in which 38 initial codes were collapsed into six subthemes and two themes. Quantitatively, students rated themselves consistently high (composite M = 4.52, SD = 0.50). Qualitatively, two themes strategic critical engagement with digital texts and evaluative and reflective reading practices accounted for the scores. Integration through a joint display showed confirmation on four dimensions and, importantly, expansion on the lowest-rated dimension: the qualitative data revealed that students detected bias by comparing across texts rather than analyzing a single text, information the questionnaire alone could not yield. Because the design is cross-sectional and relies on self-report, the findings describe students’ attained competence and reported strategies at one point in time rather than change over time or a causal effect of digital texts. The study contributes a worked example of strand integration in critical reading research and identifies within-text bias analysis as a clear instructional priority.